Long‐term clinical and radiographic evaluation after maxillary sinus floor augmentation with octacalcium phosphate–collagen composite: A retrospective case series study. (28th March 2022) - Miura, Kei‐ichiro; Sasaki, Miho; Ohba, Seigo; Noda, Sawako; Sumi, Misa; Kamakura, Shinji; Takahashi, Tetsu; Asahina, Izumi
Abstract: The purpose of this study was to evaluate, using clinical and radiological assessments, the stability of dental implants 5 years after maxillary sinus floor augmentation with octacalcium phosphate–collagen composite (OCP/Col). Maxillary sinus floor augmentation was performed through a lateral window approach. Depending on the height of the host bone, a simultaneous approach (≥5 mm) or a staged approach (less than 5 mm) was employed. The primary outcome was the evaluation of clinical dental implant conditions such as infection, peri‐implantitis, dental implant stability, pain, and paresthesia. Secondary outcomes were the evaluation of the augmented bone volume, change rate of augmented bone volume, vertical bone height, and marginal bone loss around dental implant fixture. The conditions of all dental implants were uneventful throughout the follow‐up period. Augmented bone volume and changing rate of augmented bone volume were essentially unchanged following maturation of the OCP/Col‐derived new bone. The change rate of new bone volume was 21.9% in the simulated approach and 16.8% in the staged approach at 1 year and 5 years postoperatively. The reduction rate in vertical bone height was 7.1% in the simultaneous approach and 7.5% in the staged approach between 1 year and 5 years postoperatively. Mean marginal bone loss was 1.76 mm with the simultaneous approach, and 0.50 mm with the staged approach at 5 years postoperatively. In conclusion, the success of dental implants 5 years after sinus floor augmentation by OCP/Col implantation was clarified by both clinical and radiological evaluations.